Political Relationship among Monuments: Monuments as the Subject of political Debate - Rimaitė, Viktorija (Politologija, 2019)
The aim to identify the types of political relationship among monuments can be defined as the main goal of the article. Regarding the ongoing debate about the politicization of monuments in Lithuania, the article seeks to find out what features and functions of monuments make them the subject of political controversy and political discussion. The analysis starts with theoretical assumptions distinguishing the types of relationship between monuments and politics that dominate the theoretical level. After the review of the theoretical level, the typology of the relationship between politics and monuments in Lithuania is explained highlighting the exceptions of the Lithuanian case by going through the typological analysis of the Lithuanian academic discourse.
Keywords: monuments and politics; art and politics; identity; memory; monuments